Produktivitas Ayam Arab Petelur dengan Pola Pemberian Free Feeding Choice - Eudia Christina Wulandari; Angela Nitia Nefasa (Wahana Peternakan, 2020)
The aim of the present research was to evaluate the contribution effect of feeding Wulandari et al. (2013) and Wulandari et al. (2015) rations and free feeding choice in Arab hen. One hundred birds of Arab hen, age was + 14 weeks, with an average body weight of 814,73 g ± 46,86 g were used as experimental animals, and were divided randomly into a randomized block design with 3 treatments and 6 replications. Feedstuffs used for dietary treatments were rice bran, yellow corn, fish meal, Azolla microphylla, CaCO3, oyster shell, meat bone meal, soybean meal, pollard, and top mix. The rations were formulated as ration from Wulandari et al. (2013) and Wulandari et al. (2015). At the same time, there are feedstuff which gived ad libitum without formulated. Conclusion of the research is that free feeding choice affect by palatability feedstuff and gives a random data. Consumption ration on free feeding choice more decrease than another treatments. Keywords: arab’s laying hans, free feeding choice, productivity